2010
DOI: 10.1021/nn901135b
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Bandgap-Controlled Semiconducting Single-Walled Carbon Nanotubes

Abstract: Bandgap-controlled semiconducting single-walled carbon nanotubes (s-SWNTs) were synthesized using a uniquely designed catalytic layer (Al(2)O(3)/Fe/Al(2)O(3)) and conventional thermal chemical vapor deposition. Homogeneously sized Fe catalytic nanoparticles were prepared on the Al(2)O(3) layer and their sizes were controlled by simply modulating the annealing time via heat-driven diffusion and subsequent evaporation of Fe at 800 degrees C. Transmission electron microscopy and Raman spectroscopy revealed that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
42
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 38 publications
(78 reference statements)
3
42
0
1
Order By: Relevance
“…From a literature survey, the floating catalyst method has demonstrated the widest and most precise control of SWCNT diameter (~<1 to ~2.1 nm)456. In addition, previous approaches, which used the sparse distribution of catalysts on substrates, have demonstrated a coarse control over a substantial diameter range78910. Recently, the diameter control of SWCNT forests has also showed remarkable progress3334353637.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…From a literature survey, the floating catalyst method has demonstrated the widest and most precise control of SWCNT diameter (~<1 to ~2.1 nm)456. In addition, previous approaches, which used the sparse distribution of catalysts on substrates, have demonstrated a coarse control over a substantial diameter range78910. Recently, the diameter control of SWCNT forests has also showed remarkable progress3334353637.…”
Section: Discussionmentioning
confidence: 99%
“…For substrate growth, one basic approach has demonstrated the widest range of diameter control: increase catalyst spacing to minimize unwanted particle aggregation7891011. In this manner, Lu et al reported diameter control of SWCNTs from 0.6 to 2.1 nm by selectively activating either the smaller or larger nanoparticles7.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Optimization of the pre-annealing conditions or multiple growth cycles with argon purge steps between each growth cycle led to higher SWCNT densities [22,23]. The reduction of the iron catalyst particle size during annealing has so far only been investigated for vertically aligned SWCNT forests on Al 2 O 3 and random networks [24][25][26].…”
Section: A N U S C R I P Tmentioning
confidence: 99%
“…Since the growth of single-walled CNTs is sensitive to the environmental temperature, 101 a controlled periodic temperature change in the growth process is expected to obtain a periodic change in the diameters of single-walled CNTs, 102 implying the possibility to achieve bandgap engineering within individual single-walled CNTs for the fabrication of functional devices. New electronic and optical properties can be expected from the diameter-modulated single-walled CNTs, such as improved optical absorption in solar cells by absorbing different wavelength regions in the solar spectrum in different sections of the CNTs.…”
Section: Growing Diameter-modulated Single-walled Cntsmentioning
confidence: 99%